Self-Concept and Related Factors in Children and Adolescents with Thalassemia Major Aged 7-18 in Golestan Province, 2012 - Leili Borimnejad; Ome Kolsoum Toomaj; Hamid Haghani (Golestan University of Medical Sciences, 2014)
Background and Objective: The people with Thalassemia, because of frequent blood transfusion and sever complication ,require constant medical supervision, and their psychological problems are paramount. This study aimed to determine Self-Concept and related factors in children and adolescents with Thalassemia major aged 7-18 in Golestan province ,2012. Material and Methods: This cross-sectional study was conducted on 155, using census sampling, children and adolescents with Thalassemia major refereeing to therapeutic and health centers for blood transfusion. The instruments were Piers-Harris self-concept questionnaire and demographic data . The analysis was performed by SPSS software using ANOV and t-test. Results: The mean of self-concept was low, and there was significant relationship between self-concept and variables such as age, educational status, dropout , order of birth, the number of children in family and parents' education level. But no significant difference was observed between self-concept and the factors such as sport, the frequency of transfusion, economic status. Conclusion: The results revealed that the self-concept of the thalassaemic patients is low. Some non-adjustable factors exacerbate this condition, but encouraging them to continue their education, informing their parents more about their children's disease can be helpful to improve their self-concept.